2016
DOI: 10.1177/0954407016641322
|View full text |Cite
|
Sign up to set email alerts
|

Active vehicle rollover control using a gyroscopic device

Abstract: A gyroscopic system is designed and utilized as an actuator for the prevention of vehicle rollover. The vehicle motion before rollover and during rollover is considered in two phases: before lift-off of the wheels and after lift-off of the wheels. The lateral load transfer ratio is used to identify the time when the wheels lift off the ground. Based on the equations of motion for the vehicle on two wheels, an imminent rollover algorithm is designed to specify the rollover risk. A fuzzy controller that determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…This confirms that high-speed vehicles (such as racing cars) have a low gravity center height of gravity and large width as the vehicle's design allows. All the mentioned figures are in full agreement with those obtained by: the following researchers : Lambert [6], Zuraul et al [8], Akshey khot [9], Colvin [10], Mashadi et al [12]. Gyroscope and centrifugal effect together critical speed that counted on the bases of the gyroscopic moment in addition to the centrifugal force effect , both together.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…This confirms that high-speed vehicles (such as racing cars) have a low gravity center height of gravity and large width as the vehicle's design allows. All the mentioned figures are in full agreement with those obtained by: the following researchers : Lambert [6], Zuraul et al [8], Akshey khot [9], Colvin [10], Mashadi et al [12]. Gyroscope and centrifugal effect together critical speed that counted on the bases of the gyroscopic moment in addition to the centrifugal force effect , both together.…”
Section: Resultssupporting
confidence: 88%
“…The spin speed of the rotor is high and, according to Eq. 6, other terms can be ignored to obtain a relation that enable us to estimate the rotor dimensions [12], which is:…”
Section: 1modeling Vehicle Coup Due To Gyroscopic Moment Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14] Gyro stabilization technology was first applied to two-wheeled vehicles in which the power generated by the gyroscope acted on the vehicle to keep it upright during the movement. 15 Mashadi et al 16,17 introduced a gyroscope device to prevent the vehicle from rolling over. The experimental results showed that the system can successfully stabilize the vehicle.…”
Section: Introductionmentioning
confidence: 99%